Nightly Business Report Presents Lasting Leadership : What You Can Learn from the Top 25 Business People of our Times. - Pandya, Mukul, 1957-; Brown, Jeff; Junnarkar, Sandeep; Shell, Robbie; Warner, Susan (Wharton School Publishing Pearson Education [distributor], 2004)
Annotation